Dynamic battery equalization scheme of multi-cell lithium-ion battery pack based on PSO and VUFLC. (March 2022) - Wang, Biao; Xuan, Dongji; Zhao, Xiaobo; Chen, Jiahui; Lu, Chenlei
Highlights: Dynamic battery equalization scheme of multi-cell lithium-ion battery pack. Optimize equalization energy path by particle swarm optimization. Dynamic regulation of equalization current by variable universe fuzzy logic control. Abstract: Aiming at three problems of over equalization, energy loss and time consumption, a dynamic equalization scheme is designed to control the equalization process of multi-cell Lithium-ion battery pack. First, a modified Buck-Boost circuit using inductor to transfer energy is proposed, which improves the equalization speed and is easy to realize in hardware modules. Then, for the problem of over equalization, state of charge is estimated by extreme learning machine based on genetic algorithm and used as the equalization variable. In order to improve energy utilization, particle swarm optimization is used to dynamically optimize the equalization process to obtain the optimal equalization energy path. On the basis of the optimal equalization energy path, variable universe fuzzy logic control based on fuzzy inference is used to achieve dynamic adjustment of the equalization current and reduce the time consumption. Finally, the simulation results show that the proposed equalization scheme can reduce the energy loss by 2.39%, improve the equalization speed by 36%, and effectively reduce the inconsistency of multi-cell Lithium-ion battery pack.